(untitled) (Research, Society and Development, 2022)
Osteomyelitis is an inflammation characterized by involving the medullary spaces of the bones. In the jaw, it can occur as a result of local infections, trauma, surgical procedures and caries, affecting the mandible more than the maxilla. Patients usually present with painful symptoms, edema, trismus, fever and bone sequestration. The aim of this paper is to report a case of chronic osteomyelitis associated with mandibular fracture in a pediatric patient, going through the stages of diagnosis, drug treatment and surgery. A five-year-old female patient was referred to the hospital unit with a history of inflammation in the left mandibular region and a fall from her own height. On physical examination, he presented edema in the left hemiface and fistula in the left mandibular angle region with active drainage of a purulent collection. On intraoral examination, he presented dental elements with extensive destruction by caries. The tomographic examination showed a process of osteolysis, spinal cord destruction and mandibular fracture, which, associated with the patient’s history and clinical characteristics, led to the diagnostic hypothesis of mandibular osteomyelitis associated with pathological fracture. Initially, antimicrobial therapy was instituted aiming at a less aggressive and more conservative surgical intervention, and we opted for conservative treatment of the fracture in the mandible angle region. The surgical procedure consisted of debridement of necrotic tissue and extractions. It is known that osteomyelitis in pediatric patients is relatively uncommon and that it can generate conditions that are difficult to resolve, especially when not treated quickly and early. Diagnostic delays can evolve and reach prime anatomical areas such as the cervical region and mediastinum, leading to the risk of death.